1998
DOI: 10.1119/1.18958
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous dispersion of dye solutions observed in a prismatic cuvette

Abstract: An experimental setup is described which uses a prismatic dye cuvette and a dispersion glass prism. The two prisms are oriented so as to ensure wavelength-dependent deflection in two perpendicular planes. The dispersion of the solvent material was subtracted by using an immersion cuvette filled with the solvent liquid of the dye solution. The setup displays the contribution of the dye material to the refractive index of the solution as a function of the wavelength. The setup is simple, inexpensive, does not us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
4
4
0
Order By: Relevance
“…Just like in the classical experimental setup for this phenomenon, a directional light source was placed at the thin edge of the coloured prism so that the incident rays are already split into their prismatic colours, but the absorption is still weak. The result was as expected and in accordance with the photo that can be seen in [EHB98] – the colors are separated and reversed, since the anomalous change in the refractive index is very strong in this case (figure 5a). Two things can be observed:…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Just like in the classical experimental setup for this phenomenon, a directional light source was placed at the thin edge of the coloured prism so that the incident rays are already split into their prismatic colours, but the absorption is still weak. The result was as expected and in accordance with the photo that can be seen in [EHB98] – the colors are separated and reversed, since the anomalous change in the refractive index is very strong in this case (figure 5a). Two things can be observed:…”
Section: Resultssupporting
confidence: 91%
“…Later [Kun71] and [Pfl98] as well as [Woo99] [WM01] further examined techniques to make anomalous dispersion visible and measured the change in the index of refraction. A complete review of the known techniques to observe anomalous dispersion can be found in [EHB98] where also a photo of the effect can be seen.…”
Section: Resultsmentioning
confidence: 99%
“…Similar anomalous refraction from a prism in the spectral vicinity of a resonance has been observed, e.g., in Ref. [23]…”
Section: Resultssupporting
confidence: 78%
“…[ 2,8,21 ] Here the term negative describes refraction by the surface of a medium with a negative refractive index, [ 1–3,8 ] while the term anomalous refers to a refraction angle with a wavelength dependence opposite to that associated with an ordinary glass surface. [ 21–24 ]…”
Section: Introductionmentioning
confidence: 99%
“…The composition of spectra can be easily visualized using the crossed prism method originally introduced by Newton [23,[25][26][27]. Already in his famous optics experiments, Newton studied what happened if a spectrum of light after a first prism is incident on a second prism whose orientation is perpendicular to the first.…”
Section: A Methodsmentioning
confidence: 99%